2018
DOI: 10.4317/jced.54030
|View full text |Cite
|
Sign up to set email alerts
|

Repair bond strength of composite: Effect of surface treatment and type of composite

Abstract: BackgroundBy an increase in use of composite restorations, some defects are also seen in these restorations, which need to be repaired. Since complete replacement of an old restoration may compromise the tooth structure, repair of defect is a more practical approach if there is no caries recurrence. Risk of pulp injury also decreases as such. One major challenge in restoration repair is to obtain a durable bond between the new and old composite. Laser irradiation has been suggested for surface preparation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…An important step for success of repair procedure is the surface asperization, that has the function of increasing the surface roughness and consequently increasing the bond strength by mechanical adhesion (Brunton et al, 2017). Some (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i5.14951 methods have been evaluated for this purpose, such as aluminum oxide blasting, diamond tip asperization, laser pretreatment, hydrofluoric and phosphoric acid application, among others (Duran et al, 2015;Brunton et al, 2017;De Jesus et al, 2017;Fornazari et al, 2017;Ghavam et al, 2018;Ayar et al, 2019). Microporosities creation using diamond-tip in high rotation propitiates the micro-retention of resin-based materials, showing effectiveness in adhesion increase of way practical and accessible for clinicians (De Jesus et al, 2017;Ghavam et al, 2018), thus this method was selected in the present study for roughening of aged composite.…”
Section: Discussionmentioning
confidence: 99%
“…An important step for success of repair procedure is the surface asperization, that has the function of increasing the surface roughness and consequently increasing the bond strength by mechanical adhesion (Brunton et al, 2017). Some (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i5.14951 methods have been evaluated for this purpose, such as aluminum oxide blasting, diamond tip asperization, laser pretreatment, hydrofluoric and phosphoric acid application, among others (Duran et al, 2015;Brunton et al, 2017;De Jesus et al, 2017;Fornazari et al, 2017;Ghavam et al, 2018;Ayar et al, 2019). Microporosities creation using diamond-tip in high rotation propitiates the micro-retention of resin-based materials, showing effectiveness in adhesion increase of way practical and accessible for clinicians (De Jesus et al, 2017;Ghavam et al, 2018), thus this method was selected in the present study for roughening of aged composite.…”
Section: Discussionmentioning
confidence: 99%
“…No clear information about the minimum threshold bonding strength that can be accepted for restoration repair is available (Ghavam, Naeemi, Hashemikamangar, Ebrahimi, & Kharazifard, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum repair bond strength required in the repair of restorations can be considered as a minimum of 15 MPa as mentioned in previous studies (Ghavam et al, 2018;Kiomarsi et al, 2017;Oglakci & Arhun, 2019). Thus, it is important to apply the appropriate surface treatment to restoration material while undertaking a repairing procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and mechanical damages can destroy composite restorations during their service period. Clinical studies revealed 5%-45% failure rate during a 5-year period in this regard (1)(2)(3). It has been demonstrated in a clinically simulated study that more than twice as much tooth structure is lost when removing composite restorations than comparable amalgam restorations (4).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the bond will be so weak if the adhesive is not applied after surface preparation (16,25). Despite many studies, there is still no agreement on the best composite repair protocol (2,11,26,27). Therefore, a combination of mechanical/chemical preparation and bonding agents has been used in this regard (28,29).…”
Section: Introductionmentioning
confidence: 99%